Fifty Years of Empirical Research on Country-of-Origin Effects on Consumer Behavior: A Meta-Analysis - Samiee, Saeed; Leonidou, Leonidas C.; Aykol, Bilge; Stöttinger, Barbara; Christodoulides, Paul (My University, 2016)
Country-of-origin (COO) effects, defined as the influence of foreignness of products/services on consumer choice behavior (Samiee 2011), has been one of the most frequently investigated topics in the field of international marketing. Although a significant amount of scholarly work has been published on the subject over the last five decades, there is little consensus over its nature and conceptualization, internal validity, importance to consumers, and relevance to managers, given the globalization of markets, uncertainties regarding the accuracy of consumers’ knowledge of the true COO, and different regulations among countries regarding the disclosure of COO information (e.g., Harzing and Josiassen 2008; Magnusson et al. 2011; Roth and Diamantopoulos 2009; Samiee 2010, 2011; Samiee and Leonidou 2011; Samiee et al. 2005; Usunier 2006). This body of research has also been criticized as being too fragmented, inconsistent, and non-programmatic to yield a clear picture on the subject (Samiee 1994).
Keywords: Country-of-origin (COO); International marketing; Customer Relationship Management; Brand Image; Consumer Involvement